The Development of Administration model for STEM Education Under the Office of the Secondary Education Service Area 27 - ทานะเวช นายเกรียงไกร; อินต๊ะเสนา อัฐพล (Chophayom Journal, 2019)
This research study has two objectives: 1) to identify factors and the indicators of administration for STEM education under the Office of the Secondary Education Service Area 27. 2) to investigate its ideal situation of administration for STEM education under the Office of the Secondary Education Service Area 27. The study consisted of two steps. In the first step, five experts were selected using the purposive sampling in order to identify both the factors and indicators of administration for STEM education under the Office of the Secondary Education Service Area 27. In the second step, the researcher used the stratified random sampling in order to select 260 samples from various groups as follows: school directors, deputy directors department of Academic Affairs, heads of science department, heads of mathematics department, heads of career and technology department from educational institutions under the Office of the Secondary Education Service Area 27. After that, analysis of current situation, ideal situation and needs assessment as a guide to the study best practice for the development of administration model for STEM education under the Office of the Secondary Education Service Area 27. The tools used in the research are the evaluation form, of identify factors, the indicators and questionnaire. The statistics used in the research were the Mean, Standard Deviation and the PNI. The results showed that: 1) there were seven factors and 43 indicators of administration for STEM education under the Office of the Secondary Education Service Area 27. The first factor were policy formulation and organization planning, the second factor was curriculum development, the third factor was the development of teachers’ performance, the fourth factor was learning administration, the fifth factor were supervision and evaluation, the sixth factor was networking for development and the last factor were research and development. The results of the assessment of suitability and feasibility of administration for STEM education under the Office of the Secondary Education Service Area 27 were at the highest level. 2) The current situation of administration for STEM education under the Office of the Secondary Education Service Area 27 was at moderate level ( = 3.40, S.D. = 1.04) and the level of ideal situation of administration for STEM education at high ( = 4.49, S.D. = 0.67). In order of modified Priority Need Index (PNI) from most to least were networking for development, research and development, curriculum development, learning administration, supervision and evaluation, the development of teachers’ performance and policy formulation and organization planning, respectively. Keywords : Administration model for STEM Education